Genetic and phenotypic analysis of novel South African Avian poxviruses - Carulei, Olivia (Department of Pathology, 2019)
Avian poxviruses are important pathogens of both wild and domestic birds and exhibit a large degree of intragenus diversity at a genomic level. These viruses are known to differ in growth characteristics (in vitro and in vivo), virulence, and cross-protection, with little known about the genomic contributions to these differences. Only six isolates from subclades A and B and one from proposed subclade E have had their genomes completely sequenced. These genomes have been shown to exhibit typical poxvirus genome characteristics with conserved central regions and more variable terminal regions, however all isolates exhibit major differences in defined central regions. This study aimed to analyze and characterize novel isolates from South Africa in terms of growth characteristics and phylogenetic relationships. It also added to the pool of genome sequences available for comparative genomic analyses to further investigate genome architecture. Poxvirus isolates from lesser flamingo (Phoenicopterus minor) and African penguin (Spheniscus demersus) were chosen for analysis from a larger pool of donated isolates by comparison of macroscopic growth characteristics on chorioallantoic membranes, membrane histology and phylogenetic analyses based on nucleotide alignment of partial P4b sequences. Flamingopox virus was shown to group in subclade A3, induce membrane thickening and mesodermal hyperplasia while Penguinpox virus grouped in subclade A2, and did not induce membrane thickening or hyperplasia. The genomes of the above isolates were sequenced and compared to other available avipoxvirus genomes. Dotplot comparisons revealed major differences in central regions that have traditionally been thought to be conserved. Further analysis revealed five regions of difference, of varying lengths, spread across the central regions of the various genomes. Although individual gene identities at the nucleotide level did not vary greatly, gene content and synteny between isolates/species at these identified regions were far more divergent than expected. The reasons for these large genomic rearrangements are yet to be elucidated and will need to be considered in future phylogenetic studies and vaccine vector design. Sequencing and analysis of further avian poxvirus genomes will help characterize this complex genus of poxviruses.